Supporting language and communication : a guide for school support staff - Sage, Rosemary (Rosemary Joy Wysall Beaton) (Supporting learning professionally., 2006)
Examining aspects of communication, this book considers how a positive learning environment can nurture a good understanding of communication. It will help teaching assistants to acquire skills and strategies that they can call on to provide optimum support when working with children in a variety of situations, in both primary and early years settings. Contents include: an exploration of current issues, such as the difference between home and school language; how to communicate material and information effectively to pupils; a consideration of the needs of particular groups of speakers; what m.